Stress in college students (Research, Society and Development, 2023)
Stress is a reaction of the body to an event considered challenging, in which there are psychological, physical and hormonal responses, culminating in the breakdown of homeostasis. University students represent significant samples of groups affected by stress. Based on this, the study aimed to carry out an analysis of the scientific production on stress in university students. This is a literature review using the databases: Pubmed, Scielo and Virtual Health Library – (BVS), using the descriptors: stress, students and university students. The results showed that the professionalization process in a Higher Education Institution - HEI, triggers a series of emotional changes in the student, which can impact the quality of training, which culminates in the need for HEIs to identify students with pathological stress, concomitantly with carrying out actions aimed at mental health. Based on the study, it was concluded that there is a high occurrence of stress in university students.